On the solvability of implicit differential inclusions - Arutyunov, Aram; Oliveira, Valeriano Antunes de [UNESP]; Lobo Pereira, Fernando; Zhukovskiy, Evgeniy; Zhukovskiy, Sergey (Taylor & Francis, 2014)
In the paper, the set-valued covering mappings are studied. The statements on solvability, solution estimates, and well-posedness of inclusions with conditionally covering mappings are proved. The results obtained are applied to the investigation of differential inclusions unsolved for the unknown function. The statements on solvability, solution estimates, and well-posedness of these inclusions are derived.
Keywords: conditionally covering mapping; Lipschitz perturbation; implicit differential inclusion; 47J22; 34A60